Using multi-beam optical tweezers to create optical lattices and manipulate micro-particles. (September 2021) - Soleimani, Ali; Zakery, Abdolnasser
Highlights: 1 Factors affecting the force on a particle located in an optical lattice have been investigated. 2 Gradient and scattering forces on the arbitrary size particle are determined. 3 Decomposition of conservative and non-conservative parts of the total force is carried out. 4 Effect of polarization in multi-beam optical tweezer for optical manipulation was investigated. 5 Factors affecting the potential energy of a particle in an optical lattice are investigated. 6 Influence of beam angles on particle potential energy is investigated in some detail. Abstract: Using multi-beam optical tweezers is an effective and convenient way to create optical lattices and manipulate micro-particles. We study how the number of incident beams and polarization state of them and their angle of incidence influence the optical force resulting from optical lattices created on the plane of boundary to semi-infinite media on an arbitrary size dielectric spherical particle. Furthermore, based on Cartesian multi-pole expansion theory, we decomposed optical force exerted on a spherical dielectric into the gradient (conservative part) and scattering force (non-conservative part) for both Mie particles as the general case often used in laboratories and Rayleigh particles as a limited case to show that our calculations are correct. The decomposition of optical force is extremely important to optical tweezer, and it will help us understand the physical mechanism during the multi-beam trapping. Moreover, we investigate those particles' potential energy, which gives a comprehensive insight into particle trapping and the orientation of forces on the particle. Also, by examining the potential energy of the particle, the trapping stiffness can be obtained. We believe that our studies can provide helpful insights into using multi-beam optical tweezers for experimental investigators in particle arrangement or particle sorting.